An Evaluation of the Effect of Therapeutic Ultrasound on Healing of Mandibular Fracture. Issue 4 (December 2015) - Patel, Kiran; Kumar, Sanjeev; Kathiriya, Nishtha; Madan, Sonal; Shah, Ankit; Venkataraghavan, Karthik; Jani, Mehul
The mandible is the most frequently fractured bone in maxillofacial trauma, the treatment of which consists of reduction and fixation of dislocated fragments by open or closed approach. Innovative techniques toward reducing the period of the postoperative intermaxillary fixation (IMF) are being researched. A relatively unknown treatment that may have an effect on fracture healing is ultrasound. Recent clinical trials have shown that low-intensity pulsed ultrasound (LIPUS) has a positive effect on bone healing. The aim of this study was to evaluate the effect of LIPUS on healing by its application in fresh, minimally displaced or undisplaced mandibular fracture in young and healthy individuals. A total of 28 healthy patients were selected randomly from the outpatient department needing treatment of mandibular fractures. They were then randomly allocated to either of the following two groups—experimental group and study group. After IMF, patients in experimental group received pulsed ultrasound signals with frequency of 1 MHz, with temporal and spatial intensity of 1.5 W/cm 2, pulsed wave for 5 minutes on every alternate day for 24 days, whereas patients in control group received no therapy except IMF. Radiographic density at the fracture zone was assessed from the radiograph by Emago (Emago, Amsterdam, Netherlands) Image Analysis software before IMF then at 1st to 5th weeks post-IMF. The amount of clinical mobility between fracture fragments was assessed by digital manipulation of fractured fragment with the help of periodontal pocket depth measuring probe in millimeters at pre-IMF and after 3 weeks. Pain was objectively measured using a visual analogue scale at weekly interval. The data collected were subjected to unpaired " t " test. The experimental group showed significant improvement in radiographic density compared with control group at 3- and 5-week interval; pain perception was significantly reduced in experimental group compared with study group in the subsequent weeks. No significant difference was found in clinical mobility between fracture fragments at 3-week interval. The present study provides a basis for application of therapeutic controlled ultrasound as an effective treatment modality to accelerate healing of fresh, minimally displaced mandibular fracture.